Plant functional remote sensing and smart farming applications - Omasa, Kenji; Ono, Eiichi; Ishigami, Yasuhiro; Shimizu, Yo; Araki, Yoichi (International Journal of Agricultural and Biological Engineering, 2022)
Plants have the distinctive 3D spatial structure that varies among organs, species and communities, and the spatial structure changes as they interact with their environments. The functions linked to fundamental biological activities such as transpiration, photosynthesis, and growth are also affected by the spatial structure and the environment. In order to promote smart farming using information and communication technology (ICT), it is necessary to measure and utilize information at the cell-organ of plants to the individual and the community levels and the environments in two or even three dimensions. Therefore, this paper introduced the outline of remote sensing of plant functioning and examples of the 3D remote sensing from relatively short distances using drones and ground Lidar. The quality control of rice in the paddy field and chlorophyll fluorescence imaging for photosynthetic diagnosis were also introduced. In addition, a field smart farm and a smart greenhouse, which heavily utilize ICT, built at Takasaki University of Health and Welfare in Gunma, Japan, were also introduced. Keywords: remote sensing, smart farming, smart greenhouse, IoT, ICT, image analysis DOI: 10.25165/j.ijabe.20221504.7375 Citation: Omasa K, Ono E, Ishigami Y, Shimizu Y, Araki Y. Plant functional remote sensing and smart farming applications. Int J Agric & Biol Eng, 2022; 15(4): 1–6.